2020
DOI: 10.19087/jveteriner.2020.21.4.637
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Dengue Hemorrhagic Fever Cases in Ternate City, North Moluccas

Abstract: Dengue Hemorrhagic Fever (DHF) is an endemic disease and it’s still a health problem in Ternate City. DHF is reported to occur every year and spread throughout the Districts in the Ternate Island region. Studies with epidemiological approaches according to people, places, and times that describe the incidence of DHF within a period of 10 years need to be known as an evaluation in the control program. The variables examined in this study were gender, age, number of deaths, the incidence of DHF in the subdistric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
2
5
0
3
Order By: Relevance
“…Six of the seven DHF patients reported in the second spreadsheet were under 14 years of age and more were male. This is in line with previous studies showing that the majority of DHF incidences occur in the 5-14 year age group, where at that age the immune system is still low so that age is one of the risk factors for the incidence of DHF [5]. According to Kasman in Tomia et al, gender can affect the incidence of DHF due to mobility factors which basically men spend more time outside the house so they have a high risk of being bitten by mosquitoes [5].…”
Section: Discussionsupporting
confidence: 92%
“…Six of the seven DHF patients reported in the second spreadsheet were under 14 years of age and more were male. This is in line with previous studies showing that the majority of DHF incidences occur in the 5-14 year age group, where at that age the immune system is still low so that age is one of the risk factors for the incidence of DHF [5]. According to Kasman in Tomia et al, gender can affect the incidence of DHF due to mobility factors which basically men spend more time outside the house so they have a high risk of being bitten by mosquitoes [5].…”
Section: Discussionsupporting
confidence: 92%
“…This study shows that men were registered with the highest number of DHF cases annually, both in non-COVID and COVID-19 pandemic conditions. The results of this study are consistent with several previous studies, which showed that in 2009-2018 in Ternate City, there were more DHF sufferers among men (507 people) than among women (411 people) (12). Another study conducted in Banjarmasin in 2012-2016 also stated that more DHF cases were found in men (147 subjects) than in women (98 subjects) (13).…”
Section: Pattern Of Dengue Hemorrhagic Fever (Dhf) Cases Based On Personsupporting
confidence: 92%
“…The incidence of DHF increased significantly among the age group of 5-14 years suffers from DHF because of the activity pattern of this age group, which was similar and matched with the peak pattern of Aedes aegypti mosquito activity, which is on 08.00-09.00, when children are doing activities in school, and on 16.00-17.00, when children are doing activities around the house (18). Low body resistance and high activity increases the risk of being bitten by mosquitoes (12).…”
Section: Pattern Of Dengue Hemorrhagic Fever (Dhf) Cases Based On Personmentioning
confidence: 99%
“…Until now, there are 4 provinces with a very high number of DHF cases in Indonesia, namely, East Java (340 cases), West Java (270 cases), Central Java (213 cases), and East Kalimantan (103 cases) (Arisanti et al, 2021). The lowest number of cases was achieved by Papua (0 cases), NTT and West Sulawesi (2 cases), and the Bangka Belitung Islands (3 cases) (Tomia et al, 2020). Overall Indonesia is considered high because the IR is 78.0 (Arisanti et al, 2021).…”
Section: A B S T R a Kmentioning
confidence: 99%